2011
DOI: 10.1523/jneurosci.0151-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Chorda Tympani Nerve Terminal Field Maturation and Maintenance Is Severely Altered Following Changes to Gustatory Nerve Input to the Nucleus of the Solitary Tract

Abstract: Neural competition among multiple inputs can affect the refinement and maintenance of terminal fields in sensory systems. In the rat gustatory system, the chorda tympani, greater superficial petrosal, and glossopharyngeal nerves have distinct but overlapping terminal fields in the first central relay, the nucleus of the solitary tract (NTS). This overlap is largest at early postnatal ages followed by a significant refinement and pruning of the fields over a three-week period, suggesting that competitive mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 53 publications
(95 reference statements)
5
35
0
Order By: Relevance
“…More specifically, at adulthood, the appearance of CT and GSP terminal fields reverts to an immature organization (Zheng et al, 2014), becoming diffusely distributed without this neural activity. This return to an immature terminal field pattern has been reported in other studies on gustatory terminal field development and plasticity and suggested to be the default organization in the absence of neural activity and synaptic competition (May and Hill, 2006;Corson and Hill, 2011;Sun et al, 2017). It appears, however, that a threshold of duration and/or magnitude of altered taste-elicited activity is necessary to alter terminal field organization at adulthood.…”
Section: Role Of Neural Activity In Nst Terminal Field Development Ansupporting
confidence: 80%
See 1 more Smart Citation
“…More specifically, at adulthood, the appearance of CT and GSP terminal fields reverts to an immature organization (Zheng et al, 2014), becoming diffusely distributed without this neural activity. This return to an immature terminal field pattern has been reported in other studies on gustatory terminal field development and plasticity and suggested to be the default organization in the absence of neural activity and synaptic competition (May and Hill, 2006;Corson and Hill, 2011;Sun et al, 2017). It appears, however, that a threshold of duration and/or magnitude of altered taste-elicited activity is necessary to alter terminal field organization at adulthood.…”
Section: Role Of Neural Activity In Nst Terminal Field Development Ansupporting
confidence: 80%
“…For example, functional taste responses in the NST can be modified by learning and taste experience at adulthood (Giza and Scott, 1983;Chang and Scott, 1984;Giza et al, 1997). Moreover, the anatomical terminal field organization of the rat CT reverts to the immature pattern of enlarged terminal fields when the GSP and IX are cut at adulthood (Corson and Hill, 2011). Although findings from this study suggest that a life-long plasticity exists in CT terminal fields, it did not directly test the hypothesis that taste-elicited activity maintains gustatory terminal fields at adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the role of lack of sodium salt taste on the development of terminal field organization in the rostral NST, we used mice described in detail by Chandrashekar et al (2010). Briefly, the ␣-subunit of the epithelial sodium channel (␣ENaC) was conditionally deleted in taste bud cells by crossing mice that drove the expression of Cre-recombinase under the cytokeratin 19 (CreK19) promotor (Chandrashekar et al, 2010) with mice that were a homozygous mutant for the floxed Scnn1a (␣ENaC) gene (Scnn1a flox/flox ;Hummler et al, 2002). The CreK19 mice were generously supplied by Dr. Charles Zuker, Columbia University, and Dr. Edith Hummler, University of Lausanne, Switzerland, supplied the Scnn1a flox/flox mice.…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…Moreover, they found that adult mice lacking the functional sodium salt taste transducer throughout life had a selective suppression of salt taste responses from the chorda tympani (CT) nerve, which innervates taste buds on the anterior tongue. They also demonstrated that mice lacking the functional transducer for salt taste lacked the appropriate behavioral responses driven by NaCl (Chandrashekar et al, 2010). This knockout mouse is an ideal experimental model to ask questions related to the role of taste elicited activity on the development and plasticity of central gustatory circuits for multiple reasons.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation